2017
DOI: 10.3390/app7010043
|View full text |Cite
|
Sign up to set email alerts
|

Property Analysis of Exfoliated Graphite Nanoplatelets Modified Asphalt Model Using Molecular Dynamics (MD) Method

Abstract: This Molecular Dynamics (MD) simulation paper presents a physical property comparison study between exfoliated graphite nanoplatelets (xGNP) modified and control asphalt models, including density, glass transition temperature, viscosity and thermal conductivity. The three-component control asphalt model consists of asphaltenes, aromatics, and saturates based on previous references. The xGNP asphalt model was built by incorporating an xGNP and control asphalt model and controlling mass ratios to represent the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It is worth noting that there are other in silico approaches that are capable of providing more accurate estimations of the binding affinity [31], but the improvement is attained at the expense of a significant increased computing time. The method that we have used though it delivers more rough binding estimations, importantly it still can rank correctly the binding affinities of a group of ligands at a reduced computing cost, which may potentially be valuable to the rapid identification of ligands that bind the protein receptor with higher affinity, which could lead to the development of new drugs.…”
Section: Binding Energy and Ligand-receptor Interactionsmentioning
confidence: 99%
“…It is worth noting that there are other in silico approaches that are capable of providing more accurate estimations of the binding affinity [31], but the improvement is attained at the expense of a significant increased computing time. The method that we have used though it delivers more rough binding estimations, importantly it still can rank correctly the binding affinities of a group of ligands at a reduced computing cost, which may potentially be valuable to the rapid identification of ligands that bind the protein receptor with higher affinity, which could lead to the development of new drugs.…”
Section: Binding Energy and Ligand-receptor Interactionsmentioning
confidence: 99%
“…However, it is not taken into account that some oxidation reaction occurs during the aging procedure. So another approach has been proposed by Yao et al [110] and Xu and Wang [108]. Yao added a carboxylic acid group on the asphaltenes molecule to represent aged asphaltenes.…”
Section: Aged Asphalt Bindermentioning
confidence: 99%
“…Nanotubes. Yao et al compared the two models of the asphalt binder with exfoliated graphite nanoplatelets (xGNP) and control asphalt binder by means of MD simulation to study the physical and thermal properties of the xGNP-modified asphalt binder [110].…”
Section: Graphene and Carbonmentioning
confidence: 99%
“…Li et al established an asphalt mastic model with a low silica particle content and found that the selective adsorption between silica particles and polar components in asphalt is the potential reason for the physicochemical interaction [ 42 ]. Additionally, the exploration of the thermodynamic and mechanical behaviors of nanoparticle-modified asphalt had been conducted through MD simulations, such as adding nano hydrated lime [ 43 ], nano-ZnO [ 44 ], graphite nanoplatelets [ 45 , 46 ], and carbon-nanotubes [ 47 ]. It is worth mentioning that Long et al analyzed the interfacial adhesion properties of nano-silica modified asphalt mastic through MD simulation.…”
Section: Introductionmentioning
confidence: 99%